THE EFFECTIVENESS OF COLLABORATIVE WRITING TO IMPROVE THE STUDENTS' WRITING SKILL - Sukmawati Yasim; Musdaria; Amrang (elstic : english language linguistics culture, 2022)
This study aims to determine whether collaborative writing is effective to improve students' writing skills or not and to know students' perceptions of collaborative writing. This research was conducted at SMAN 3 Majene. The samples of the research were 40 students from grade X or tenth grade. The researchers employed mixed research methods. Researcher used tests to collect data about the ability to write descriptive texts and interviews as research instruments to collect data about the extent of the influence of collaborative writing on motivation and self-confidence in learning. The data analysis technique uses Statistical Product and Service Solution (SPSS) 20 to analyze quantitative data and qualitative descriptive analysis techniques to analyze qualitative data and the results of this study indicate that there is an effect of collaborative writing on learning motivation. Based on the results of the N-Gain score test which were analyzed using SPSS, it showed that the average N-Gain score for the experimental group (collaborative writing) was 52.5034. It is categorized less effective category with a minimum N-Gain value of 36, 17% and a maximum value of 66.67%, it indicates that the effect of collaborative writing on students' learning motivation is able to improve students' writing skills with category less effective. Thus, this collaborative writing is recommended to improve students’ writing skills.